MANAGEMENT OF SUICIDAL CUT THROAT-A CASE REPORT: Management of Suicidal Cut Throat - Ashfaq, Kamran; Ahmed, Attique; Shah, Amanat Ali; Khan, Maryam (Pakistan Armed Forces Medical Journal, 2015)
INTRODUCTION Suicide is one of the 10 leading causes of death in the world, accounting for more than 400,000 deaths annually1. Hanging, poisoning and fire arm are the most common methods of committing suicide in the world. Knives and razor blades are the common implements used in suicide2. Tentative marks were present in most fatalities3. Suicide by cutting one’s own throat without hesitation cuts remains rare. Such life threatening injuries require emergency treatment3,4. Here we present a case of young individual presenting in ENT department Combined Military Hospital (CMH) Quetta with a suicidal cut throat injury, using a long bladed knife.